IMPLEMENTATION OF NON-COMPETITION CLAUSE AS THE BASIS OF TRADE SECRET PROTECTION IN INDONESIA - Sartika Nanda Lestari; Sakhiyatu Sova; Rinitami Njatrijani (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Each company has trade strategies that should not be known by other parties; therefore, Trade Secret is necessary to protect them. Trade secret emerges from an agreement between employees and company, one of which is by implementing Non-Competition Clause in that agreement. This article accordingly discusses how the implementation of Non-Competition Clause and the legal consequence of the implementation of Non-Competition Clause as the form of trade secret protection. Regarding the issue discussed in this paper, the result shows that the implementation of Non-Competition Clause in employment agreement must be conducted based on Trade Secret Law which causes legal consequence like employees prohibitions as an effort to keep their commercial in confidence. However, the implementation of Non-Competition Clause has not been effectively implemented for there is no detailed explanation in the agreement resulting in the different clause interpretation between company and employees. Therefore, it is necessary to have separated and detailed regulation concerning Non-Competition Clause in the employment agreement.Keywords: non-competition clause, employment agreement, trade secret